2018
DOI: 10.1088/1755-1315/102/1/012006
|View full text |Cite
|
Sign up to set email alerts
|

The potential of avocado paste (Persea americana) as fat substitute in non-dairy ice cream

Abstract: Abstract. Consumer preferences towards plant-based food have shifted significantly due to sustainable and healthy reasons. Dairy products consist of high Saturated Fatty Acid (SFA) and overconsumption of SFA could lead to cardiovascular diseases. Avocado contains high levels of fat dominated by Monounsaturated Fatty Acid (MUFA) and phytosterol that have the potential as a plant-based fat source to substitute dairy-fat in ice cream. The objective of this study was to analyze the physicochemical, rheological and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Consuming dietary fibre provides many benefits, and frozen dessert with a higher fibre content can offer additional nutritional benefits and help to meet daily dietary fibre intake requirements. Total solids have an inverse relationship with moisture content, which is consistent with the findings of Ervina et al (2018). The higher solid content found in SMP control, 3CP3SM-SO and 3CP3SM-CO could be attributed to the fact that a lower amount of water was added to their formulations.…”
Section: Physicochemical Propertiessupporting
confidence: 87%
See 1 more Smart Citation
“…Consuming dietary fibre provides many benefits, and frozen dessert with a higher fibre content can offer additional nutritional benefits and help to meet daily dietary fibre intake requirements. Total solids have an inverse relationship with moisture content, which is consistent with the findings of Ervina et al (2018). The higher solid content found in SMP control, 3CP3SM-SO and 3CP3SM-CO could be attributed to the fact that a lower amount of water was added to their formulations.…”
Section: Physicochemical Propertiessupporting
confidence: 87%
“…Total solids have an inverse relationship with moisture content, which is consistent with the findings of Ervina et al . (2018). The higher solid content found in SMP control, 3CP3SM‐SO and 3CP3SM‐CO could be attributed to the fact that a lower amount of water was added to their formulations.…”
Section: Resultsmentioning
confidence: 99%
“…The differences of texture may not be the results of the different flavours use. The texture differences can occur due to the variation of the ice cream machine during processing such as temperature and mixing control [16]. However, there were no significant differences observed for vanilla taste and vanilla aroma attributes as well as for aroma and taste of milk suggesting that these flavours can be used interchangeable since there were no significant differences for their aroma and taste attributes.…”
Section: The Sensory Profiles Of Soft Ice Cream With the Natural And ...mentioning
confidence: 95%
“…Two different formulations were used comparing the artificial and natural vanilla flavour. The main ingredients of the soft ice cream follow a study reported by Ervina [16] with some modifications. The main ingredients such as milk, skim-milk powder, glucose syrups, maltodextrin, stabilizer and emulsifier were mix together with other additional ingredients (flavour, salt).…”
Section: Sample Preparationsmentioning
confidence: 99%
See 1 more Smart Citation